The application of platelet‐rich plasma for skin graft enrichment: A meta‐analysis - Chen, Jianguo (Int Wound J, 2020)
Existing evidence demonstrated that the role of platelet‐rich plasma (PRP) in skin graft enrichment is uncertain. The aim of this study was to evaluate the efficacy and safety of PRP for skin graft. PubMed, EMBASE, Web of Science, and Cochrane Library databases were searched for randomised controlled trials that compared outcomes of skin graft treated with PRP versus those treated with blank controls. The outcomes mainly included the rate of skin graft take, number of skin graft loss and haematoma formation, and complications. There were 11 studies involving a total of 910 cases of skin grafts. Compared with the control group, PRP group had a significantly higher rate of skin graft take (mean difference = 5.47%; 95% confidence interval [CI], 2.80%‐8.14%; P < .0001), fewer number of skin graft loss (risk ratio [RR] = 0.26; 95% CI, 0.13‐0.55; P = .0004) and fewer cases of haematoma formation (RR = 0.24; 95% CI, 0.11‐0.54; P = .0006). There was no significant difference in the incidence of complications between two groups. This meta‐analysis summarises current evidence and indicates that PRP is a safe and effective adjuvant for skin graft enrichment.